Technological Possibilities of EDUSAT - Rout, Sarat Kumar (JOURNAL OF INDIAN EDUCATION, 2010)
With the increase in development of science and technology, there is change in pattern and innovation in educational system. Satellite communitcation technology presents its special advantage and speciality. It brings new vigor to education. The article presents about how India has used its satellite for the educational purpose. It widens the teaching scale and contents of radio, television and in universities. It improves the development of training for secondary and primary teachers and of vocational education. It pushes forward the educational reform and economic and educational development for the country. India is making efforts on transforming the educational satellite net to digital, interactive and Ku wave system with the development of information technology. The article also focuses on getting feedback about use of the Information technology resources. It concludes that interactive teaching and transformed educational satellite net will play an important role in the country’s distance education.